SOUNDPET (INTEGRATED/0918/0008); Piccolo Grande Guerriero ‐ Associazione Malattia PMLD, Grant/Award Number: 2020‐22 Grant - Damianou, Christakis A. (My University, 2026)
Christakis Damianou, PhD, an electrical engineering professor at the Cyprus University of Technology, was recently awarded a €1 million grant to develop an MR-guided focused ultrasound system for use in dogs and cats. The device, called SOUNDPET, is a preclinical robotic system for use in small and large animals. “After development, the system will be evaluated in phantoms, excised tissue, and animals,” said Dr. Damianou. “The same mechanisms that result in cancer in humans are operative in pets and in other animals as well. Man’s best friend is probably man’s best new biomedical friend.” The first application that the device will be used for is naturally occurring mammary cancer. It has been designed to have four degrees of freedom that can sonicate phantoms, excised tissue, and animals. Additional components of the design include: A single element transducer that ranges from 2 to 6 cm in diameter An operating frequency of 0.5 to 4 MHz Tissue heating monitoring via MR thermometry Operating software Eventually the system will be modified for use in humans by scaling up the design of the robotic system, but the proposed technology will first serve the veterinary community. The long-term goal is to commercialize this technology, and the device should be in final product form by the end of the project. Besides the Cyprus University of Technology, the other partners are MEDSONIC, the German Oncology Center, and the Department of Cyprus Electromechanical services. The project started July 2020 and will be completed June 2023. The study was co-financed by the European structural and investment funds and the Republic of Cyprus through the Research and Innovation Foundation under the project SOUNDPET (INTEGRATED/0918/0008). https://www.fusfoundation.org/posts/cyprus-veterinary-team-receives-1m-focused-ultrasound-grant/
Keywords: Sciences